2010
DOI: 10.1016/j.jtcvs.2009.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of deep sternal wound infections after coronary artery bypass grafting by means of injection of platelet gel: An evolving technology

Abstract: pulmonary atresia, (2) associated with systemic obstruction-aortic arch interruption, and (3) with unrestricted systemic and pulmonary flows. PFAA might be asymptomatic when it forms a subclavian artery arising from the ascending aorta (type A3) 3 or a double-lumen (subway) type of aortic arch in the absence of aortic interruption or coarctation (type A1). 1 No intervention is needed in such patients. At the other end of the spectrum, it might be an isolated anomaly connecting the ascending aorta to the PA, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…And it turns out to be effective in improving the healing of ulcers [1, 2]. Risk of infection decreases after the use of APG on surgical wounds, in addition to its effect on facilitating healing [3]. One study has revealed the antibacterial activity of APG against Staphylococcus aureus [4], and similar results have been shown in our previous research [5].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…And it turns out to be effective in improving the healing of ulcers [1, 2]. Risk of infection decreases after the use of APG on surgical wounds, in addition to its effect on facilitating healing [3]. One study has revealed the antibacterial activity of APG against Staphylococcus aureus [4], and similar results have been shown in our previous research [5].…”
Section: Introductionsupporting
confidence: 58%
“…Although decreased infection rate was observed by Kachel [3], more research of the antibacterial activity of APG in vivo should be done.…”
Section: Discussionmentioning
confidence: 99%
“…These factors play important roles in wound healing. [8,9] In addition, platelets have antimicrobial activity. [10,11] The rationale behind using fibrin glue that it behaves as a provisional matrix and actively recruits cells to trigger fibrin-mediated responses, such as cell adhesion, migration, proliferation and tubule formation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, few studies in cardiac surgery, applied autologous platelet gel on the wound surface area at the end of the operation as prophylaxis against wound infection rather than as therapy for established DSWI. [8] PFG has been applied for treatment of other chronic wounds In a retrospective cohort study on the effectiveness of autologous platelet releasate in the treatment of diabetic neuropathic foot ulcers, Margolis et al showed that platelet releasate was more likely to be used in more severe wounds and was also more effective in treating these wounds than the standard of care. [13] In a prospective non-blinded study, Crovetti et al showed the efficacy of once-weekly applications of either autologous or homologous origin platelet gel in healing cutaneous chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that this is a promising technique, with the result that the delivery of autologous platelet growth factors and vital neutrophilic leucocytes is now gaining more popularity. However, randomized controlled studies to support the use of PG in cardiac surgery are mandatory, but it is also difficult to execute such a study because these patients have a number of confounding factors which need to be compensated for, and therefore large patient groups are necessary order to achieve statistical significance [44].…”
Section: Clinical Studiesmentioning
confidence: 99%